Implementação de um modelo de geometric semantic genetic programming para aplicação naval - Fonseca, Pedro Eduardo Quadrado da (2016)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management